Incidence of Obesity in Diabetes Mellitus Rates, Profile of Teachers and Employees at SMA X Surabaya - Noer kumala indahsari; Olivia Herliani; Suhartati Suhartati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Reduced metabolic function can cause the human body to experience a lack of energy, resulting in the possibility of diseases including diabetes mellitus, hypertension, atherosclerosis, and even coronary heart disease. Objective: This study aims to analyze the incidence of obesity through Body Mass Index on the incidence of diabetes mellitus and Lipid Profile at SMA X Surabaya. Methods: The research design used was cross-sectional. Sampling was carried out using non-probability sampling with a random sampling technique. Data collection was carried out at SMA X Surabaya by 64 teachers and employees of SMA X Surabaya. Respondents were gathered to receive health education, then went through the registration stages, and vital signs, and then 5 mL of venous blood was taken to measure blood sugar levels and lipid profiles, namely total cholesterol and triglyceride levels. This research uses the Chi-Square test statistical test. Result: There is a significant relationship based on the chi square test between body mass index and cholesterol levels and triglyceride levels. because the p-value < 0.05 is 0.041 and 0.050 respectively, but there is no significant relationship between body mass index and glucose levels with a p-value of 0.181. Conclusion: There is a relationship between the incidence of obesity through Body Mass Index and the incidence of Lipid Profile but there is no relationship with the incidence of diabetes mellitus at SMA X Surabaya